A novel peak shaving approach to improving load flexibility of the Allam cycle by integrating cold energy storage. (1st February 2023) - Xie, Meina; Chen, Longxiang; Wu, Kai; Liu, Zekun; Lin, Jian; Jiang, Chenxing; Xie, Shan; Zhao, Yingru
Abstract: Allam cycle is a promising alternative cycle for power generation, characterized by high net electrical efficiency and near-zero emissions. For efficient and load flexible operation, a novel system integrating Allam cycle and cold energy storage system (CES-Allam) has been proposed. The compression train is employed to increase the pressure of CO2 -rich working fluid for both Allam and refrigeration subsystems. The ice slurry is used as a cold energy storage carrier, which is further used to assist in liquefying carbon dioxide (CO2 ) at a lower evaporating pressure, and leads to higher electrical power output during peak load hours. The thermodynamic and economic models of this integrated system have been developed for comprehensive evaluation. The results show that the proposed integrated system is technically feasible for load flexible operation with a wider range of power generation regulation capacity (28.46%–105.97%) than that of the conventional Allam system (40%–100%). The round trip efficiency is 71.09% for the cold energy storage system, which is equivalent to the adiabatic compressed air energy storage system. The payback period is 4.15 years for the cold energy storage subsystem, which indicates that the CES-Allam system is economically feasible and competitive. Moreover, the sensitivity analyses of electricity prices and natural gas shows that the proposed CES-Allam system is more suitable for areas with higher natural gas prices and greater differences in peak and valley electricity prices. The present study is expected to provide a detailed reference and guidance for the use of cold energy storage to improve the load flexibility of the Allam system. Highlights: A novel peak shaving system is proposed that integrates Allam cycle and cold energy storage system. Cold energy is used to liquefy CO2 and leads to higher electrical power output during the peak period. Compression train in the Allam system is also employed by the refrigeration system to reduce the investment cost. The proposed system can be operated flexibly in a wider range of power generation regulations.